2014
DOI: 10.1128/aem.00687-14
|View full text |Cite
|
Sign up to set email alerts
|

Novel Outer Membrane Protein Involved in Cellulose and Cellooligosaccharide Degradation by Cytophaga hutchinsonii

Abstract: bCytophaga hutchinsonii is an aerobic cellulolytic soil bacterium which was reported to use a novel contact-dependent strategy to degrade cellulose. It was speculated that cellooligosaccharides were transported into the periplasm for further digestion. In this study, we reported that most of the endoglucanase and ␤-glucosidase activity was distributed on the cell surface of C. hutchinsonii. Cellobiose and part of the cellulose could be hydrolyzed to glucose on the cell surface. However, the cell surface cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…C. hutchinsonii may thus adopt an alternative mode of utilization in which the cell surface enzymes of C. hutchinsonii digest cellulose extracellularly to cellobiose and glucose, eliminating the need for SusC-like and SusD-like proteins to import longer oligosaccharides. A recent study showed that extracted outer membrane proteins containing endoglucanase and ␤-glucosidase activities had the ability to hydrolyze cellulose to glucose in vitro (6). Interference with the efficient hydrolysis of cellobiose into glucose resulting from the absence of an outer membrane protein, CHU_1277, was further found to compromise the ability of C. hutchinsonii to assimilate cellulose (6).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…C. hutchinsonii may thus adopt an alternative mode of utilization in which the cell surface enzymes of C. hutchinsonii digest cellulose extracellularly to cellobiose and glucose, eliminating the need for SusC-like and SusD-like proteins to import longer oligosaccharides. A recent study showed that extracted outer membrane proteins containing endoglucanase and ␤-glucosidase activities had the ability to hydrolyze cellulose to glucose in vitro (6). Interference with the efficient hydrolysis of cellobiose into glucose resulting from the absence of an outer membrane protein, CHU_1277, was further found to compromise the ability of C. hutchinsonii to assimilate cellulose (6).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that extracted outer membrane proteins containing endoglucanase and ␤-glucosidase activities had the ability to hydrolyze cellulose to glucose in vitro (6). Interference with the efficient hydrolysis of cellobiose into glucose resulting from the absence of an outer membrane protein, CHU_1277, was further found to compromise the ability of C. hutchinsonii to assimilate cellulose (6). In the present study, we identified CHU_1276, a gene locus upstream of CHU_1277, whose disruption not only compromised the efficient hydrolysis of cellobiose, but also affected the uptake of glucose at a low concentration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations